HEALTHY LEARNING ENVIRONMENT DI LEMBAGA PENDIDIKAN ANAK USIA DINI - Hasanah, Fitria Fauziah; Prameswari, Woro; Kustanti, Rizqi; Nurassyfa, Rania Nataesa (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Creating a healthy learning environment for early childhood is very important because the environment will affect children's learning. If the learning environment is not healthy, then the child will experience difficulties in learning. Children find it difficult to focus because they feel worried for their safety and comfort. Children need to gain a sense of trust that they are in a healthy environment, so that children can learn optimally. This research is a qualitative research with data collection techniques including interviews, observation, and documentation. The research was conducted at RA Asiyah Ciawi Tasikmalaya. Based on the results of the research, it shows that schools manage the learning environment in order to create a healthy environment including several aspects, namely 1) Classroom arrangement; 2) Adequate lighting, 3) Good air (temperature and ventilation), 4) Pay attention to safety, and 5) School cleanliness.